2013
DOI: 10.1063/1.4819747
|View full text |Cite
|
Sign up to set email alerts
|

Bio-electrospraying of human mesenchymal stem cells: An alternative for tissue engineering

Abstract: Bio-electrospraying (BES) is a technique used for the processing of cells and can be applied to tissue engineering. The association of BES with scaffold production techniques has been shown to be an interesting strategy for the production of biomaterials with cells homogeneously distributed in the entire structure. Various studies have evaluated the effects of BES on different cell types. However, until the present moment, no studies have evaluated the impact of BES time on mesenchymal stem cells (MSC). Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 30 publications
6
36
0
Order By: Relevance
“…The electrostatic repulsion between the positive charges present in the needles used in polymer electrospinning and the cell electrospraying syringes was probably the cause of the displacement of the bioelectrospraying jet away from the Petri dish. This observation is corroborated by the fact that when just the bioelectrospraying was conducted in a previous study, 14 cell recovery was about 83%. The effect was also observed by Stankus et al 10 In their work, the repulsion from Coulombic forces caused a small area of electrospinning and electrospraying convergence.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…The electrostatic repulsion between the positive charges present in the needles used in polymer electrospinning and the cell electrospraying syringes was probably the cause of the displacement of the bioelectrospraying jet away from the Petri dish. This observation is corroborated by the fact that when just the bioelectrospraying was conducted in a previous study, 14 cell recovery was about 83%. The effect was also observed by Stankus et al 10 In their work, the repulsion from Coulombic forces caused a small area of electrospinning and electrospraying convergence.…”
supporting
confidence: 67%
“…In a previous study, 14 the concentration of 3×10 6 cells/mL was used to conduct the standardization of bioelectrospraying parameters. However, when the bioelectrospraying was associated with electrospinning, suspensions with low cell concentrations yielded SCCs with poor cellular densities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sahoo et al demonstrated bone marrow stem cells (BMSCs) electrosprayed at 7.5kV retain their multipotency and differentiate into adipogenic, chondrogenic, and osteogenic lineages although cell viability decreased with increasing applied voltages [16] . Furthermore, other studies focusing on applied voltage, needle diameter, polymer concentration and cell density effects confirm that the EHD processing technique does not impose detrimental effects on cell viability [13b, 16] , and that applied voltages between 0kV and 20kV as well as flow rate had no obvious effect on human stem cell survival [17] . To this end, fabricated functional living constructs may be explored for repair and replacement of damaged or degenerating tissues or organs, and/or for delivery of personalised medicines in a controlled and localised manner.…”
Section: Ehd Spraying Technologymentioning
confidence: 61%
“…In other studies, BES was used to process mesenchymal stem cells and human adipose-derived stem cells. 170,171 In both cases, the viability and proliferative capacity of electrosprayed cells remained intact compared to that of the controls (without undergoing electrical stress) as no changes in cellular metabolism, plasticity, or immunophenotypic profile were observed, although a breakdown of cellular DNA was detected in case of mesenchymal stem cells. However, the exact reason for the damage is still not clear, although genotoxic effects of electromagnetic fields could be a possible cause.…”
Section: Bioelectrospraying and Cell Electrospinningmentioning
confidence: 71%